The effect of digital marketing, and e-commence on SMEs performance of Baghdad - Mechman, Ali; Omar, Siti Sarah; Hamawandy, Nawzad Majeed; Abdullah, Arshad Sedeeq; Qader, Abdulkhaleq Nader (2022)
The Service of SMEs at present is categorized by intensive competition and quick changes in client expectations, improving regulatory standards, innovation in technology and increased competition. The review of the literature investigated the relevant studies on digital marketing, and e-commerce, and SME's performance. The theoretical framework was based on the hypothesis of the resource perspective. Built on the central assumption which states that, digital marketing and e-commerce are greatly related to SME's performance. The present paper seeks to describe The Relationship of digital marketing and e-commerce in enhancing Iraqi SMEs. In this research, 228 respondents were investigated within the SMEs services and industries in Baghdad, Iraq. Smart PLS 3.2.9 was used to analyse the results. The results of the paper found a range of assumptions and conclusions are as follows. It was revealed that the increasing interest in handling digital marketing and e-commerce and its effect on the establishment of SME's performance competitiveness. The findings also indicated a positive effect on SME's performance in digital marketing and e-commerce variables. This Mirrors the potential of the sector to offer excellent performance as a strong indicator.